A noção de justiça para além da ética de Emmanuel Lévinas, em Autrement qu'être - Leonardo Meirelles Ribeiro (2017)
From the verification of a terminological conflict established between the notions of ethics and justice in Totalité et infini and Autrement qu'être, and the questioning of the possibility of reconciling these two terms in the 3rd. section Du Dire au Dit ou la Sagesse du Désir, from chapter V of Autrement qu'être, by Emmanuel Lévinas, the present thesis analyzes the possibility of answer by means of a notion presented at the end of that section, in which Lévinas defines philosophy as "Wisdom of love at the service of love". Content that seems to guide the relationship between Saying and said, as the same as Du Dire au Dit in-form justice, love will bring us the possibility of a conceptual relationship between ethics and justice where, in our view, justice appears as beyond ethics. That is, if in that section, on the one hand, justice is presented as a limitation of ethics, on the other hand, it means and is possible as an extension or ilimitation of ethics. This is the paradox to be confirmed, aided by the parallel analysis, and no less necessary, of the original "writing" of Lévinas to allow (or not) such conciliation, which we believe to come from a "logic of ambiguity" permeating his discourse. In this sense, the paradox in Lévinas does not come to make difficult, but, inversely, it comes to aid the understanding of the apparent conflict between the two terms.